Implementasi Maslahah dalam Pertimbangan Hakim pada Penetapan Dispensasi Nikah Pasca Revisi Undang-Undang Perkawinan: Studi Kasus Pengadilan Agama Jember - Abdul Ghofi Dwi Setiawan (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2024)
The increase in marriage dispensation applications following the amendment of Law Number 16 of 2019 reflects new dynamics in the practice of religious courts. This study aims to analyze judicial considerations in deciding marriage dispensation cases at the Religious Court of Jember and to identify the dominant underlying factors. This field research employs a qualitative method with a juridical-empirical approach. Primary data were obtained through interviews with judges, while secondary data were derived from statutory regulations, legal literature, and court decisions. The findings indicate a significant rise in applications in 2022, with the majority of cases granted. The dominant factors include premarital pregnancy, parental pressure, economic constraints, weak religious education, social media influence, concerns over social stigma, and the impact of changes in the minimum marriage age regulation. Judges’ considerations are based on normative (Qur’anic and Islamic legal maxims), juridical, sociological, and public interest (ijtihad) perspectives. The novelty of this study lies in examining the shift in judicial reasoning patterns after the amendment of Law 16/2019, highlighting a stronger emphasis on sociological analysis and the prevention of greater harm. These findings demonstrate the dialectical relationship between positive legal norms and social realities in religious court practice.